123I-FP-CIT brain SPECT (DaTSCAN) imaging in the diagnosis of patients with movement disorders: First results - Jauković Ljiljana; Ilić Tihomir V.; Dopuđa Marija; Ajdinović Boris (Vojnosanitetski Pregled)
Background/Aim. 123I-FP-CIT brain single-photon emission computed tomography (SPECT), DaTSCAN imaging, offers a possibility to study structural and biochemical integrity of presinaptic dopaminergic neurotransmitter system. The aim of this study was to evaluate the usefulness of 123I-FP-CIT brain SPECT scintigraphy in patients with extrapyramidal diseases. Methods. Fifteen patients (8 males and 7 females), aged 26-81 years, presenting with extrapyramidal symptoms entered the study. Out of them, 7 patients were diagnosed with definite clinical form of idiopathic Parkinson’s disease (PD) or clinical probable for PD clinical stage 2-4 using the Hoehn&Yahr scale (H&Y); 6 patients were with atypical parkinsonism (AP), 1 patient with essential, and 1 with psychogenic tremor. SPECT was performed 180 min after injection of 185 MBq 123IFP- CIT using a dual head Gamma camera. Sixty four one minutes’ frames were acquired using a noncircular rotation mode into a 128 × 128 image matrix. Transverse slices were reconstructed using a 0.6 order Butterworth filter. Visual interpretation was based on striatal uptake, left to right asymmetry and substructures most affected. The ratio of binding for the entire striatum, caudate and putamen to nonspecific binding in occipital cortex was calculated. SPECT findings were categorized as normal and abnormal (incipient, moderate and severe presinaptic deficit). Results. 123I-FP-CIT uptake was reduced in the striatum of 6/7 patients with PD and 5/6 patients with AP. Two patients with PD and AP showed a negative finding. The remaining 2 negative results were obtained in the patients diagnosed with essential tremor and psychogenic tremor. The mean striato-occipital ratio (SDR) of the most affected side was lower in the patients with PD. Conclusion. Our first results confirm the usefulness of 123I-FPCIT brain SPECT in differential diagnosis of extrapyramidal diseases.